Mudanças no Conteúdo de Matemática Escolar: efeitos na (re)elaboração do conteúdo de estatística do livro didático - LIMA, Pablo Henrique Mendes (Universidade Federal do Tocantins, 2023)
The central theme addressed in this work corresponds to the possible changes in relation to the content of school mathematics, specifically basic education in the content of statistics. We problematize the production of the curriculum, here, to seek what should be the curriculum, and what are the knowledge considered as rights to be said in schools, in the sense of understanding in schools, in the sense of understanding how some factors that influence the changes of these contents in the Textbook. LD). For this discussion, we brought the readings of the documents that regulate education in Brazil, others from the field of curriculum theories and Statistics education. Thus, the main objective of the project is to understand how the discourses materialized in official education documents and in the work performed will influence changes in the content of statistics in textbooks. It is one that uses documental analysis, through the survey of collections of textbooks from Elementary School II, from the National Textbook Plan of 2020, used by the 62 schools that are guided by the Regional Board of Education of Araguaína, culminating in in the treatment and analysis of information from the two most used editions of the collection. As the A Conquista da Matemática collection was the most used, it was noticed from the analysis that, in relation to the 1998 edition, in the edition published in 2018 there was an expansion and deepening of the statistical concepts and tools to be taught and learned. In view of this, it is concluded that there have been significant changes in the way in which the content of Statistics is presented/mobilized in the editions of LDs analyzed.